Spatiotemporally Precise Optical Manipulation of Intracellular Molecular Activities - Bin Dong; Shivam Mahapatra; Matthew G. Clark; Mark S. Carlsen; Karsten J. Mohn; Seohee Ma; Kent A. Brasseale III; Grace Crim; Chi Zhang (Advanced Science, 2024)
Abstract Controlling chemical processes in live cells is a challenging task. The spatial heterogeneity of biochemical reactions in cells is often overlooked by conventional means of incubating cells with desired chemicals. A comprehensive understanding of spatially diverse biochemical processes requires precise control over molecular activities at the subcellular level. Herein, a closed‐loop optoelectronic control system is developed that allows the manipulation of biomolecular activities in live cells at high spatiotemporal precision. Chemical‐selective fluorescence signals are utilized to command lasers that trigger specific chemical processes or control the activation of photoswitchable inhibitors at desired targets. This technology is fully compatible with laser scanning confocal fluorescence microscopes. The authors demonstrate selective interactions of a 405 nm laser with targeted organelles and simultaneous monitoring of cell responses by fluorescent protein signals. Notably, blue laser interaction with the endoplasmic reticulum leads to a more pronounced reduction in cytosolic green fluorescent protein signals in comparison to that with nuclei and lipid droplets. Moreover, when combined with a photoswitchable inhibitor, microtubule polymerization is selectively inhibited within the subcellular compartments. This technology enables subcellular spatiotemporal optical manipulation over chemical processes and drug activities, exclusively at desired targets, while minimizing undesired effects on non‐targeted locations.